Is air pollution detrimental to regional innovation? An empirical heterogeneity test based on Chinese cities - Liao, Zhilin; Hu, Mingxing; Gao, Lei; Cheng, Baodong; Tao, Chenlu; Akhtar, Rizwan (Frontiers in Public Health, 2022)
Nowadays innovation seems to be the inevitable choice to achieve stable economic growth. However, the negative impact of air pollution on health and economy makes air pollution an important factor in regional innovation, which deserves our discussion. The overall regional innovation level from 2014 to 2019 has an upward trend while the overall air pollution has a downward trend during the period, which provides foundation for our research. Based on the data of 285 prefecture level cities in China from 2014 to 2019, this paper uses the mediation and fixed effect model to verify the impact and mechanism of air pollution on regional innovation. The results show that the increase of air pollution, measured by the air quality index, significantly inhibits regional innovation. Air pollution has significant funds crowding-out effect and human capital loss effect, thereby decreasing the regional innovation level, which means innovation funds and researchers play a mediating role between air pollution and regional innovation. In heterogeneity analysis, it is found that the detrimental effect of air pollution on regional innovation is significant in eastern and central China, in large and medium-sized cities, and in cities with poor or general air quality. It indicates that developed and large regions should pay more attention to air pollution control. For polluted regions, more emphasis and endeavors are needed to address air pollution problems. Besides, the inhibitory effect is more severe on incremental innovation rather than radical innovation, which deserves the attention of enterprises engaged in incremental innovation. Therefore, we propose that targeted environmental policies and effective measures should be developed to improve air quality in the long run. Moreover, policymakers could provide strong support for innovation grants, talent subsidies and rewards, and encourage clean technological innovation through short-term trade-offs between high polluting and low polluting enterprises.